COMMUNITY PARTICIPATION IN SCHOOL-BASED MANAGEMENT AT SDN 2 JETIS TO FACE THE DIGITAL ERA - Desi Ratnasari; Roemintoyo .; Winarno . (Universitas Muhammadiyah Ponorogo, 2018)
Community participation is crucial in the successful implementation of school- based management. Educational challenges for educators in the current digital era are very heavy. Technological advances require that creative educators innovate in learning, as well as schools should pay close attention to school management. However, community participation is also needed to overcome the challenges of education in the digital era. The puspose of this study is to determine the role of the community in the implementation of school-based management to deal with the digital era. This research method is a qualitative research method. From the results of interviews and observations, SDN 02 Jetis always empowers the community in every school activity and invites the community to participate in the progress of the students achievements and cooperates in supervising the progress of students achivements. The principal of SDN 02 Jetis invites the community to participate in improving the achievement of learners especially in facing the challenges in the digital era.